2014
DOI: 10.1016/j.cub.2014.09.047
|View full text |Cite
|
Sign up to set email alerts
|

A Migrating Ciliary Gate Compartmentalizes the Site of Axoneme Assembly in Drosophila Spermatids

Abstract: SUMMARY Background In most cells, the cilium is formed within a compartment separated from the cytoplasm. Entry into the ciliary compartment is regulated by a specialized gate located at the base of the cilium in a region known as the transition zone. The transition zone is closely associated with multiple structures of the ciliary base including the centriole, axoneme, and ciliary membrane. However, the contribution of these structures to the ciliary gate remains unclear. Results Here, we report that in Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
130
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(148 citation statements)
references
References 45 publications
(64 reference statements)
13
130
3
Order By: Relevance
“…We recorded MRCs and TEPs from bristles in homozygote and hemizygote mecA 101 and found that they lack MRCs, but are able to maintain normal TEPs (Figure 1 C-E). The severity of the MRC is similar to that of asterless mecD , oseg2 mecE , and cep290 mecH mutants that lack functional sensory cilia (Avidor-Reiss et al 2004;Blachon et al 2008;Basiri et al 2014), suggesting that mecA 101 flies have severe defects in the function or formation of the mechanosensory neuron.…”
Section: Meca Mutant Flies Have No Mechanoreceptor Currentmentioning
confidence: 70%
See 3 more Smart Citations
“…We recorded MRCs and TEPs from bristles in homozygote and hemizygote mecA 101 and found that they lack MRCs, but are able to maintain normal TEPs (Figure 1 C-E). The severity of the MRC is similar to that of asterless mecD , oseg2 mecE , and cep290 mecH mutants that lack functional sensory cilia (Avidor-Reiss et al 2004;Blachon et al 2008;Basiri et al 2014), suggesting that mecA 101 flies have severe defects in the function or formation of the mechanosensory neuron.…”
Section: Meca Mutant Flies Have No Mechanoreceptor Currentmentioning
confidence: 70%
“…In addition, the cell bodies of those sensory neurons that lack dendrites are often clustered together ( Figure 1F). The mechanosensory organ defects displayed by mecA 101 are more severe than those observed in mutations that specifically affect components of the sensory cilium; in such mutations the dendrite extends to the base of the socket, and absence or clustering of neuronal cell bodies is not observed (Avidor-Reiss et al 2004;Blachon et al 2008;Basiri et al 2014). However, the mecA phenotype resembles that of nompA, which also often fails to innervate the bristle base.…”
Section: Meca Mutant Flies Have No Mechanoreceptor Currentmentioning
confidence: 99%
See 2 more Smart Citations
“…Note: This table is not an exhaustive list of all centrosome and cilia components mapped. Due to space constrain, only references for mutants and/or markers for each gene are mentioned in the list [15,16,19,21,31,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Also, for more information about the genes visit www.flybase.org.…”
Section: Visualizing Directly or Immunostaining Of Centrosomes And CImentioning
confidence: 99%